Studies of material migration and deposition after the 2017 experimental campaign in EAST. (March 2022) - Yan, Rong; Peng, Jiao; Li, Changjun; Xu, Guoliang; Ding, Rui; Zheng, Wei; Gao, Binfu; Zhu, Dahuan; Wang, Baoguo; Mu, Lei; Chen, Junling; Gou, Fujun; et al.
Abstract: Plasma-wall interaction is one of the key issues in tokamaks, as the material erosion and deposition will strongly influence the lifetime of plasma facing materials, fuel retention and plasma performance. Material migration and deposition have been firstly analyzed after the 2017 experimental campaign in EAST with tungsten (W) upper divertor, molybdenum inner wall and graphite lower divertor. It is found that the deposited elements on plasma-facing materials (PFMs) mainly consisted of Li, C, O, W and Mo etc, which was from the deposition of wall conditioning material and the sputtering of PFMs. More than 90 wt% of the deposits were lithium carbonate and lithium hydroxide due to the routine lithium wall conditioning in EAST. Quantitative characterization of element density on graphite tile from lower inner divertor showed that W and Mo deposition increased when closer to the lower divertor, which is consistent with the decreasing normalized poloidal magnetic flux. The element composition of PFMs along poloidal direction has been measured by handheld X-ray fluorescence (XRF). The concentration of deposited Mo and W is less than 0.2 wt% on most of the PFM surface. Double peaks of W concentration near the upper W divertor and at the midplane tile were observed on the TZM inner wall surface at the high-field side, which can be explained by higher redeposition at the location near the upper inner divertor or with a smaller normalized poloidal magnetic flux. Besides, more redeposited Mo and W was found at the inner and outer divertor near strike points compared with the dome region.